A Character-based Model for Interactive Storytelling in Games - Lima, Edirlei; Feijó, Bruno; Furtado, Antonio (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
In this paper, we present a novel character-based model for interactive storytelling in games, which combines multi-agent planning with a drama management strategy based on production rules to guide the narrative generation process. The underlying proposed method is capable of generating and controlling the enactment of character-based narratives in highly interactive game worlds. After describing the model, the paper proceeds to assess its applicability and performance. A fully implemented prototype game is used to demonstrate how the model works in practice.